Randomized clinical trial to evaluate mometasone lavage vs spray for patients with chronic rhinosinusitis without nasal polyps who have not undergone sinus surgery. Issue 8 (29th May 2020) - Jiramongkolchai, Pawina; Peterson, Andrew; Kallogjeri, Dorina; Lee, Jake J.; Kukuljan, Sara; Liebendorfer, Adam; Schneider, John S.; Klatt‐Cromwell, Cristine N.; Drescher, Andrew J.; Piccirillo, Jay F.
Abstract : Background: There is no consensus regarding the best route of intranasal delivery of corticosteroids in the treatment of chronic rhinosinusitis (CRS). The study objective of this work was to compare the impact of mometasone furoate nasal spray (MFNS) vs mometasone nasal irrigation in the management of CRS patients who have not undergone sinus surgery. Methods: A double‐blind, placebo‐controlled, randomized clinical trial was conducted in adults with CRS. Individuals with nasal polyps and/or history of sinus surgery were excluded. Patients were randomized to receive 8 weeks of either MFNS or mometasone nasal irrigation. The primary outcome measure was change in the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) score between the 2 groups. Secondary outcome measures included patient global response to treatment and Lund‐Kennedy endoscopy scores. Results: A total of 43 participants completed the study (n = 22, MFNS; n = 21, mometasone nasal irrigation). Fourteen (64%) participants in the MFNS group and 17 (81%) in the mometasone lavage group had a clinically meaningful improvement in SNOT‐22 scores with a proportion difference of 17% (95% confidence interval [CI], −9% to 44%). The least‐squares (LS) mean difference between the 2 groups for SNOT‐22 was −8.6 (95% CI, −17.7 to 0.58; p = 0.07), whereas the LS mean difference between the 2 groups for Lund‐Kennedy endoscopy scores was 0.16 (95% CI, −0.84 to 1.15; p = 0.75). No adverse events were associated with the study. Conclusion: Both MFNS and mometasone nasal irrigations are beneficial in symptom management of CRS. Our study suggests that patients who perform mometasone lavage do better in a clinically meaningful way, but our results are not definitive and further studies are warranted.